HOW GEOPOLITICAL TENSIONS REACT TO FINANCIAL MARKETS - Ashraf Turdialiyev; Shokhzod Khujamurotov (TADQIQOTLAR, 2025)
Abstract:Geopolitical tensions—ranging from military conflicts and trade wars to political instability—have a significant impact on global financial markets. These events often result in increased market volatility, shifts in investor sentiment, and capital flight to safe-haven assets. This article explores how financial markets respond to various types of geopolitical disruptions, analyzes historical examples such as the Russia-Ukraine conflict and U.S.-China trade war, and discusses strategies investors and policymakers use to manage geopolitical risk. The paper concludes that while short-term market reactions are often dramatic, long-term effects depend on the nature and duration of the geopolitical crisis.